Salihli Granitoid, Menderes Massif, Western Anatolia: a Sustainable Clean Energy Source for Mitigating Co2 Emissions - Baba, Alper; Chandrasekharam, Dornadula; Chandrasekharam, Dornadula; Ayzit, Tolga; Baba, Alper (My University, 2022)
Turkey has a great opportunity to promote renewable energy, which is produced from high heat-generating granitoids using EGS (Enhanced Geothermal Systems) technology. Exploiting the energy from the radiogenic granitoid will help the country save about 32211 million kg of CO2 from gas-based electricity power plants. In addition to the hydrothermal energy sources, energy from EGS will make the country free from energy deficit and provide sustainable power, water, and food. In the present paper, we assess the power generation capacity of Salihli granitoid (SG), with an outcropping area of about 100 km2 located within the western Anatolian plateau, and describe the technology involved in harnessing the heat from these granitoids. The Anatolian Plateau is known for extension tectonics and is explained by the westward tectonic escape and subduction rollback processes. The most prominent structures of western Anatolia are E-W and ENE-WSW trending graben and horst controlled by low and high-angle oblique to dip-slip normal faults, exposing the Menderes Massif. Magmatic activity in western Anatolia is mainly related to episodic-two stage extensional regime, where the early phase is characterized mainly by calc-alkaline Early-Middle Miocene felsic lavas and pyroclastic and the latter by late Miocene-Quaternary rift-related alkaline basaltic volcanism. The plutonic activity started during 12 to 15 Ma represented by SG. The heat generation capacity of the SG varies from 5.5 to 6.7 (µW/m3), while the heat flow values over SG range from 68 to 107 HF (mW/m2). These values are much higher compared to the global average crustal values.
Keywords: Renewable energy; Enhanced geothermal system; Geothermal exploration; Radiogenic granitoid